Evaluation of neuronal damage following hypoxic-ischaemic brain injury in acute and early chronic periods in neonatal rats - Kabakus, N.; Ozcan, A.; Aysun, S.; Yilmaz, B. (Wiley, 2006)
This study was undertaken to investigate the effects of neonatal cerebral hypoxic-ischaemic brain injury (HIBI) in acute and early chronic phases in the rat. HIBI was induced in 7-day-old rat pups by ligation of the right common carotid and then the pups were exposed to 1h of hypoxia in 8% oxygen. They were divided into two groups: I-day (acute phase, in the first 24 h) and 5-day (early chronic phase, 120 h). Neuropathological evaluation was performed using the hippocampus, cerebral cortex and basal ganglia on the coronal plane. The following values were obtained: (i) the ratio of the infarcted area; (ii) hemispheric atrophy/asymmetry (iii) patchy lesions confined to the thalamus, caudate and putamen; (iv) the ratio of damaged neurons to all neurons: and (v) the percentage of apoptotic neurons relative to the total neurons in all brain areas. HIBI-induced global cerebral damage and cellular damage findings did not significantly differ between the two rMps. However, they showed a tendency to recover/deteriorate in both acute and early chronic phases. The ratio of ipsi- and contra-lateral hemisphere infarct areas (20.7 and 15.7% vs. 40.1 and 26.7%, respectively), basal ganglia patchy lesion ratio (27.5 vs. 36.7%) and hemispheric atrophy/asymmetry (92.4 vs. 84.7%) were found to be lower in the rat pups in the chronic phase than those in the acute phase. In contrast, increases in the ratio of damaged neurons (16.7 vs. 13.3% in the cerebral and dorsal hippocampus. respectively) and in the ratio of apoptotic neurons (ipsi-lateral: 18 vs. 6%; contra lateral hemispheres: 3.5 vs. 1.7%. respectively) were recorded. It is concluded that cellular damage tends to deteriorate (damaged and apoptotic neurons) while global damage (cerebral infarct and patchy damage) improves with the progression of HIBI. However, further studies are needed in order to elucidate this process. Copyright (c) 2005 John Wiley & Sons, Ltd.
Keywords: hypoxia; ischaemia; brain damage; apoptosis; newborn; rat